Moderation of relation between psychological risk factors and alcohol use by sex. Issue 3 (15th March 2020) - Carroll, Haley A.; Rhew, Isaac; Larimer, Mary E.
ABSTRACT: Alcohol consumption is a significant public health concern among young adults, with most recent research suggesting that the sex gap in alcohol consumption among young adults is closing. Thus, the present study tested sex as a moderator for known risk factors for alcohol use (impulsivity, sensation seeking, mindfulness). We examined sex differences by surveying young adults (n = 1, 437) from across Washington state between 2011 and 2013 on alcohol risk factors (impulsivity, sensation seeking, mindfulness), alcohol consumption (quantity and frequency), and alcohol related negative consequences. Zero inflated Poisson and Zero inflated Negative Binomial models revealed that sex moderated the relationship between Peak Blood Alcohol Content (BAC) and impulsivity such that higher impulsivity was more strongly related to higher Peak BAC for women than for men. Overall, these results suggest that very few sex differences exist in alcohol consumption and alcohol-related negative consequences. Future research should look beyond the risk factors studied here to identify other important mechanisms that vary by sex that may be important targets for clinical or prevention efforts related to alcohol consumption.